Предмет: Алгебра, автор: anna111989

log2(x+1)+log2(x+2)=3-log2 (4)

Ответы

Автор ответа: Universalka
9
ОДЗ: x + 1 > 0  ⇒ x > - 1
         x + 2 > 0  ⇒ x > - 2
Значит окончательно: x ∈ (- 1 ; + ∞)
log _{2} (x+1)+log _{2} (x+2)=3-log _{2}4\\\\log _{2} (x+1)(x+2)=log_{2}8 -log _{2}4\\\\log _{2}(x+1)(x+2)=log _{2} \frac{8}{4} \\\\log _{2}(x+1)(x+2)=log _{2} 2\\\\(x+1)(x+2)=2\\\\ x^{2} +2x+x+2-2=0\\\\ x^{2} +3x=0\\\\ x(x+3)=0\\\\  x_{1} =0\\\\x+3=0\\\\ x_{2}=-3
x₂ = - 3 - не подходит
Ответ : 0
Похожие вопросы
Предмет: Математика, автор: Maripolya